Status ekologis mangrove Pulau Sembilan, Kabupaten Langkat Provinsi Sumatera Utara (Ecological status of mangrove of Sembilan Island, Langkat Regency, North Sumatra Province) - Ahmad Muhtadi; Rudi H. Siregar; Rusdi Leidonald; Zulham A. Harahap (Depik, 2016)
Sembilan Island was one of the 17 islands located in the East Coast of North Sumatra. This island is surrounded by mangrove with varying thickness and density. Information on the identification and potential of mangrove in this island already reported but limited to a narrow area. Information about the value and status of mangrove ecology in this island have not been written, so it was needed to carry out for a study of mangrove ecological analysis. This information could be used later as a reference in sustainable mangrove management. The objective of the study was to determine the value and ecological status of mangroves. The research was conducted in September 2015. The data were collected at 9 sampling points namely; 4 points in the east, 2 points in the south and 3 points in the west part of the study areas. The spot check method was used in the study. The results showed that there were 28 species of mangrove belonging to 13 families. It's divided into 26 species of true mangrove and two species of associated mangroves. Mangroves zonation was Avicennia/Sonneratia on the front and ferns (A. Aureum and A. speciosum) in the section near the mainland. Mangrove thickness reached 134 - 1683 m. The density of mangrove was 333 - 4601 individuals/ha with the cover area of 2522 - 5810 cm2/ha. The results of the importance index value of mangrove showed that A. marina has a great influence and role in the community of mangrove vegetation, especially in the eastern part. Therefore, the mangrove in Sembilan Island was categorized into damage to good condition. The good category was recorded in the western part of the island, while the damaged category was found in the east part of the island.Pulau Sembilan merupakan satu diantara 17 pulau yang terdapat di wilayah Pantai Timur Sumatera Utara. Hampir sepanjang pantai di Pulau Sembilan di tumbuhi oleh mangrove dengan ketebalan yang bervariasi. Informasi tentang identifikasi dan potensi mangrove di Pulau Sembilan sudah ada dilaporkan, namun terbatas pada areal yang sempit. Informasi tentang nilai dan status ekologi mangrove di Pulau Sembilan belum dilaporkan, sehingga perlu adanya kajian tentang analisis ekologi mangrove. Informasi ini nantinya dapat dijadikan sebagai acuan dalam pengelolaan mangrove yang berkelanjutan. Penelitian ini bertujuan untuk mengetahui nilai dan status ekologis mangrove di Pulau Sembilan. Lokasi penelitian dibagi menjadi tiga area dengan 9 titik pengamatan yaitu timur 4 titik, selatan 2 titik, dan barat 3 titik. Penelitian dilaksanakan pada September 2015. Pengambilan contoh mangrove, dilakukan dengan menggunakan metode spot check. Hasil penelitian didapatkan bahwa jenis mangrove yang sebanyak 28 jenis dari 13 famili yang terdiri dari 26 jenis mangrove sejati dan 2 jenis mangrove ikutan. Zonasi mangrove di Pulau Sembilan yaitu, Avicennia/Sonneratia pada bagian depan dan paku-pakuan (A. Aureum dan A. speciosum) pada bagian yang dekat daratan. Ketebalan mangrove mencapai 134 - 1683 m. Kerapatan mangrove yang ditemukan mencapai 333 - 4601 ind/ha. Penutupan mangrove mencapai 2522 - 5810 cm2/ha. Hasil analisis nilai penting jenis mangrove di Pulau Sembilan menunjukkan bahwa A. marina memiliki pengaruh dan peran yang besar dalam komunitas vegetasi mangrove, terutama pada bagian timur. Mangrove di Pulau Sembilan termasuk kategori rusak - baik. Kategori baik pada bagian barat dan rusak pada bagian timur.